2014
DOI: 10.1179/1754762814y.0000000093
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ‘Fitting to Outcomes Expert’ FOXwith new cochlear implant users in a multi-centre study

Abstract: FOX computer-assisted fitting can be successfully used at switch on, in different clinical environments, reducing fitting time in the first 2 weeks and is efficient at providing a usable program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…All subjects had been fitted with the HiRes Optima (Sequential) sound processing strategy and an input dynamic range of 80 dB on their everyday processors. Program parameters were set according to the FOX target driven, computer-assisted approach described in Govaerts et al [ 14 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…All subjects had been fitted with the HiRes Optima (Sequential) sound processing strategy and an input dynamic range of 80 dB on their everyday processors. Program parameters were set according to the FOX target driven, computer-assisted approach described in Govaerts et al [ 14 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies have shown that FOX was successful in systematically improving the results of the psychoacoustic test outcomes (audiometric thresholds, A §E phoneme discrimination, A §E loudness scaling, speech audiogram), especially in the first few months after switch on (Vaerenberg et al, 2011(Vaerenberg et al, , 2014a. A prospective multicenter randomized controlled trial showed that the speech audiometric results 6 months after switch-on with a target-driven, FOX-assisted approach was equivalent to or better than a conventional manual approach (Battmer et al, 2015). Even in long-term and well-fitted subjects, FOX has improved the measurable outcomes in seven out of 10 cases (Buechner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A literature review found no other studies that assessed recipient set stimulation levels and its impact on performance outcome measures. The only other more non-traditional method of CI fittings reviewed in the literature was Battmer et al (29). The “Fitting to Outcomes eXpert” (FOX), employed by The Eargroup (Antwerp, Belgium).…”
Section: Discussionmentioning
confidence: 99%
“…Battmer et al (29), investigated speech understanding and fitting times in a group of patients activated with FOX versus a standard clinical activation. Unfortunately, the groups were poorly matched for duration of deafness and a direct comparison for speech outcomes could not be completed.…”
Section: Discussionmentioning
confidence: 99%